Wrażliwość dochodów jednostek samorządu terytorialnego na wahania cyklu koniunkturalnego - Walasik, Artur (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper focuses on the concept of distribution of cyclical driven risk amongcentral and local governments. Elasticity and stabilization revenues are theoreticallyas well as empirically examined. The correlation between business cycle andfiscal efficiency of main sources of local government revenues were also studiedand the results are discussed. Own revenues, general purpose and specific purposegrants-in-aid are separately studied in detail.